The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2008
DOI: 10.1002/adfm.200800371
|View full text |Cite
|
Sign up to set email alerts
|

Motility of Metal Nanoparticles in Silicon and Induced Anisotropic Silicon Etching

Abstract: The autonomous motion behavior of metal particles in Si, and the consequential anisotropic etching of silicon and production of Si nanostructures, in particular, Si nanowire arrays in oxidizing hydrofluoric acid solution, has been systematically investigated. It is found that the autonomous motion of metal particles (Ag and Au) in Si is highly uniform, yet directional and preferential along the [100] crystallographic orientation of Si, rather than always being normal to the silicon surface. An electrokinetic m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

14
402
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 445 publications
(430 citation statements)
references
References 64 publications
14
402
0
1
Order By: Relevance
“…As sacrificial templates, SiNWs determines the location and orientation of the final AgNLs (SI, S3). Since the fabrication of SiNWs is well developed and the controlled transfer of SiNWs is obtained by contact printing, the site-specific synthesis of AgNLs or their arrays could also be realized [19][20][21][22][23]. Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…As sacrificial templates, SiNWs determines the location and orientation of the final AgNLs (SI, S3). Since the fabrication of SiNWs is well developed and the controlled transfer of SiNWs is obtained by contact printing, the site-specific synthesis of AgNLs or their arrays could also be realized [19][20][21][22][23]. Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Inspired by the metal nanoparticles' etching of Si wafer [19,20], we assembled Ag nanoparticles into a necklace with dense "hot spots" spread in 3-dimension by sacrificing SiNWs templates. Meanwhile, due to the facile transfer and high adhesion between the SiNWs and flexible PDMS films, AgNLs could be located on the surface of PDMA on the fixed position.…”
Section: Resultsmentioning
confidence: 99%
“…occur at 516 cm 21 and 510 cm 21 (Fig. 9b), has an asymmetric line shape with asymmetry appearing on the lower (red) energy side indicative of phonon confinement due to reduced sizes, as the doping density remains invariant for the same particles and no excess heating has been applied externally or through Joule heating by the incident Raman probe beam.…”
mentioning
confidence: 99%
“…These core Si values do not correlate directly with Si or PS substrates with typical Raman peaks around 521 cm 21 but are more closely linked to the PS membranes studied by Feng et al 29 In that work, Raman spectra of PS membranes removed from anodically oxidised p-type ,100. Si substrates, showed dominant Raman shifts between 502 and 512 cm 21 . 29 The bands located near 300 cm 21 correspond to an acoustic phonon (2TA).…”
mentioning
confidence: 99%
“…[2,[47][48][49] Peng et al investigated the etching direction of both gold and silver particles, and concluded that this direction is highly uniform, does not depend on the dopant type and level of the substrate, and preferentially occurs along the (100) orientation of crystalline silicon (Figure 2.6). [50] Instead of electroless deposition of metal particles, it is also possible to deposit a thin metal film, which is patterned or annealed to create…”
Section: Wet Etchingmentioning
confidence: 99%